Translating two respiratory Chinese patent medicine package inserts based on Western orientation of theory and methodology - Yuan, Wu Yuan; Syed Abdullah, Syed Nurulakla; Abdullah, Muhammad Alif Redzuan (Human Resource Management Academic Research Society (HRMARS), 2023)
The export of Chinese patent medicine (CPM) has thrived, particularly amidst the past three years of pandemic. This study focuses on the translation of package inserts (PIs) for two respiratory Chinese patent medicines, namely Lianhua Qingwen Jiaonang and Xuanfei Baidu Keli. These medicines have been extensively utilized in China's efforts to prevent and treat Covid-19 during the epidemic period, garnering significant acclaim owing to their efficacious therapeutic properties. Drawing on Snell-Hornby's theory of an integrated approach to translation and employing a comparative analysis method between leaflets of western medicine and Chinese patent medicine, this study aims to firstly examine the package insert formats of both western medicine and Chinese patent medicine. Secondly, it seeks to determine the translation strategies employed in these two types of package inserts. Lastly, it aims to identify translation errors at both lexical and syntactical levels. Through analysis, it has been determined that the PI formats of CPM and western medicine are congruent with each other, as they both fall within the realm of medical introduction. A distinguishing feature of this textual genre lies in its specialized utilization of professional and culturally loaded terminologies and pattern sentences. Consequently, the translation strategy encompasses a taxonomy that strikes a balance between domestication and foreignization by employing methods such as calque, borrowing, and transliteration. The identification of lexical and syntactical errors in the translation of two package inserts has led to an enhanced English version that is more reliable and comprehensible.